East Central Kansas Experiment Field - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2017)
The research program at the East Central Kansas Experiment Field is designed to keep area crop producers abreast of technological advances in agronomic agriculture. Specific objectives are to 1) identify top performing varieties and hybrids of wheat, corn, soybean, and grain sorghum; 2) establish the amount of tillage and crop residue cover needed for optimum crop production; 3) evaluate weed and disease control practices using chemical, no chemical, and combination methods; and 4) test fertilizer rates, timing, and application methods for agronomic proficiency and environmental stewardship.
Keywords: weather; precipitation; soil; crops